Estimating interregional trade flows in Andalusia (Spain) - José Manuel Rueda-Cantuche (European Regional Science Association (ERSA), 2005)
Perhaps, one of the most relevant issues in constructing regional input-output tables is the estimation of interregional trade flows. Hence, the Regional Statistical Office of Andalusia (Spain) is promoting new research on survey-based estimates of trade flows between the own region and the rest of Spain. Especially, survey approach has been seen to result more reliable outcomes (Eding & Nijmeijer, 1998) than non-survey constructs. This paper will focus on survey design features, sample methods, treatment of sampling and non-sampling errors and others aspects concerning data collection and processing in the case of Andalusia (Spain).
Keywords: 330